2018
DOI: 10.14419/ijet.v7i4.20.25919
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Using Cement Kiln Dust Stabilized Roads Subbase Material

Abstract: The increase in the demand for cement to produce large quantities for the purpose of reconstruction produce a large amount of cement kilns dust accordingly. The cement kilns has a cementations property and it's using to treats soil. In this study, sand gravel soil (roads subbase) materials has been used to study the effect of the cement kiln dust (CKD) as a partial replacement with the natural dust of subbase till 20% by weight. Three tests procedures have been adopted which are density-moisture relationship, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…For instance, a mere 2.5% addition of CKD elevated the thermal conductivity (K) value from 0.251 to 0.427 W/(m•K), representing a substantial increase of 70.12%. This enhancement in thermal conductivity is attributed to the pozzolanic reaction of CKD in the soil, which leads to increased density and improved soil structure, as evidenced by the significant increase in density, CBR, and UCS observed in CKD-stabilized soils [67]. This pozzolanic reaction, crucial for soil stabilization, results in the bonding of dispersed soil particles, enhancing the soil's thermal properties [68].…”
Section: Ckd Effect On Hejaz Soil a (Thermal)mentioning
confidence: 99%
“…For instance, a mere 2.5% addition of CKD elevated the thermal conductivity (K) value from 0.251 to 0.427 W/(m•K), representing a substantial increase of 70.12%. This enhancement in thermal conductivity is attributed to the pozzolanic reaction of CKD in the soil, which leads to increased density and improved soil structure, as evidenced by the significant increase in density, CBR, and UCS observed in CKD-stabilized soils [67]. This pozzolanic reaction, crucial for soil stabilization, results in the bonding of dispersed soil particles, enhancing the soil's thermal properties [68].…”
Section: Ckd Effect On Hejaz Soil a (Thermal)mentioning
confidence: 99%
“…The ability to use the CKD as an alternative material for cement was studied by Mahdi et al ( 2018) [25]. They concluded that using 20% of CKD increased CBR value, optimum moisture content, density, and shear strength of type (B) subbase soil.…”
Section: Cement Kiln Dustmentioning
confidence: 99%
“…Mahdi et al [22] examined at the potential of using cement kiln dust to enhance the properties of sand-gravel soil. Soil samples treated with 5%, 10%, 15%, or 20% of cement kiln dust as weight replacement.…”
Section: Introductionmentioning
confidence: 99%